The Power of Cooperative Principle and Politeness Strategy in Forming Phatic Speech Acts - Rosita Ambarwati; Panji Kuncorohadi (Indonesian Journal of EFL and Linguistics, 2023)
The purpose of this study is to explore and describe the role of cooperative principles and politeness strategies in forming phatic speech acts in women's communication on Facebook. This research is qualitative research. This study applies an ethnographic approach. The data type used is qualitative in words, sentences, photographs, documents, journals, and articles. The primary data in this study is the speech of women who are divided into categories, namely adult women and adolescents. The data collection techniques are interviews, observation, and documentation. The data analysis technique used the ethnographic analysis model introduced by Spradley. The research results show that adult women implement the cooperative principles of relevance maxims and quality maxims. They also violate the cooperative principles of relevance maxim, quality maxim, and quantity maxim, while the politeness strategy applies positive politeness strategies. Negative politeness strategy, off-record strategy, and bald on-record strategies. The findings that adult women have analyzed tend to apply the maxim of relevance, violate the principle of cooperation of relevance, and use positive politeness strategies. Teenagers use phatic speech acts by applying the principles of relevance and method cooperation, violating the maxims of relevance, quantity, and quality and using positive politeness and bald off-record strategies. Overall, dominant adolescents perform phatic speech acts by applying the maxim of manner, violating the maxim of relevance, and using positive politeness strategies.